2016
DOI: 10.1007/s10393-016-1098-8
|View full text |Cite
|
Sign up to set email alerts
|

Rat-atouille: A Mixed Method Study to Characterize Rodent Hunting and Consumption in the Context of Lassa Fever

Abstract: Lassa fever is a zoonotic hemorrhagic illness predominant in areas across Nigeria, Sierra Leone, Guinea, Liberia, and southern Mali. The reservoir of Lassa virus is the multimammate mouse (Mastomys natalensis), a highly commensal species in West Africa. Primary transmission to humans occurs through direct or indirect contact with rodent body fluids such as urine, feces, saliva, or blood. Our research draws together qualitative and quantitative methods to provide a fuller and more nuanced perspective on these v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 29 publications
2
64
0
1
Order By: Relevance
“…We previously showed that hunting of small rodents is more widely distributed across age, gender lines and social groups than previously appreciated [ 14 ]. In our present study, we sought to determine whether such observations were also pertinent to other species of wild animals, in particular those species that are not present in domestic spaces (as small rodents are) and might be associated with different hunting norms.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that hunting of small rodents is more widely distributed across age, gender lines and social groups than previously appreciated [ 14 ]. In our present study, we sought to determine whether such observations were also pertinent to other species of wild animals, in particular those species that are not present in domestic spaces (as small rodents are) and might be associated with different hunting norms.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of contact that occurs during hunting and consumption of rodents were also explored as part of this study but are described in a separate paper 13. Assuming that the presence of peri-domestic rodents is related to the physical set up of domestic spaces, we paid particular attention to the construction and spatial organization of houses.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary human-to-human transmission follows contact with human bodily fluids in the household or health-care facilities, and is estimated to occur in 20% of LF cases 9. Risk factors for primary (zoonotic) transmission are unclear and possibly linked to housing10 and hunting and consumption of rodents 1113…”
Section: Introductionmentioning
confidence: 99%
“…Transmission occurs when humans come into close contact with the mouse specifically through ingestion or inhalation of mouse urine, faeces or blood. Risk factors include living in close proximity to the mice, butchering and consumption (Bonwitt et al, 2016(Bonwitt et al, , 2017.…”
Section: Lassa Fevermentioning
confidence: 99%